There's a dragon in my sleeping bag - Howe, James, 1946-; Rose, David S., 1947- (New York : Atheneum Books for Young Readers : [Maxwell Macmillan International], 1994)
Alex is intimidated by his older brother Simon's imaginary dragon, until he is able to create his own friend--a camel named Calvin.
Wilson's Children.
School Library Journal.
Child Study Children's Book Committee.
2.2
K-3
Keywords: Brothers -- Fiction; Imaginary playmates -- Fiction; Brothers -- Fiction; Imaginary playmates -- Fiction; Brothers -- Fiction; Imaginary playmates -- Fiction